The Need Analysis of Student Worksheet for Writing Drama Script of Seventh Grade Student - Simbolon, Desi Efrina; Indrawati, Sri; Ernalida, Ernalida (Universitas Pendidikan Ganesha, 2021)
This research aims to describe the results of the learners’ needs toward the drama script writing material development using a scientific approach. This research applied a qualitative approach. The data were collected with observation, questionnaire, and interview techniques. The applied instruments were observation, questionnaire, and interview. The sample consisted of learners. The findings showed that the learners needed communication and technology-based teaching materials to support their needs of drama script writing skill training. Based on the learners’ characteristics identification, they needed learning application to make the learning activities and to freely enrich the sources. They also needed interesting teaching materials that had many examples, provided writing exercises, the opportunity to interact, time to work the exercise, and space to perform. Therefore, this research proposed Moodle application as a learning material in the form of a Student Worksheet. This initial stage of research is expected to be the beginning of drama script writing material development with a scientific approach and based on Moodle. The results of the learners’ need analysis could be also used by other researchers to obtain the 21st-century learners’ characteristics.